What Are These Countries Doing Here? Analyzing Transparency in the Current Flag of Convenience Regime and Their Impact on Shipping in the Arctic - Jonathan Wood; Thomas Viguier; Emma Aschlock (Nordicum-Mediterraneum, 2021)
As countries such as the Russian Federation begin the exploration and development of alternative sea routes in the Arctic due to climate change, the private shipping industry has also begun to focus on the region. However, even with this new focus, old problems continue to fester. One such problem is Flags of Convenience, which are those countries that will flag vessels cheaply and provide little to no oversight. This paper is an exploration of the transparency and good governance of selected Flag of Convenience countries through various methods as compared to a model, highly transparent Arctic model. By attempting to flag a vessel familiar to the authors, the authors uncovered a lack of transparency in these Flag of Convenience countries, show statistical evidence of the Flag of Convenience problem already being an issue in the Arctic, and provide some policy proposals in order to help to rectify a small but growing issue of Arctic shipping.